Inventing nuclear disarmament. Issue 1 (2nd January 2019) - Ritchie, Nick
ABSTRACT: The negotiation of the Treaty on the Prohibition of Nuclear Weapons forms part of the process of 'inventing' nuclear disarmament. Inventing nuclear disarmament necessarily entails diminishing counter-vailing ideas, norms, and practices. This includes ideas and practices of nuclear deterrence and 'regimes of truth' about nuclear weapons that imbue them with value. Inventing nuclear disarmament will be a continuous process rather than an end point: always contingent, always contested, always in production.